Host susceptibility to Lernaea cyprinacea L. and its treatment in a large aquarium system - Shariff, M.; Kabata, Z.; Sommerville, Christina (Wiley, 1986)
Abstract. Host susceptibility to Lernaea cyprinacea was studied during an outbreak of the infection in an aquarium containing 58 species or stocks of fish belonging to 20 families and eight orders. L. cyprinacea was accidentally introduced on two occasions and spread through the recycling of the aquarium exposing all fish to infection. During the first outbreak only 39.7% of the fish species became infected. Approximately 17% carried a mean of less than 10 parasites and 22% carried a mean of more than 10 parasites. During the second outbreak, 6 months after the first, there was a decrease in both the prevalence and intensity of infection; only five species were infected and mean levels of infection were less than 10 per fish except for newly introduced fish. This suggests the possible development of immunity in the previously infected hosts. On both occasions the infection was successfully eradicated by using Unden (2‐isopropoxy‐phenyl‐N‐methylcarbamate) at 0.16 ppm, weekly for 4 weeks and Dipterex (0,0‐dimethyl, 2,2,2‐trichloro‐l‐hydroxyethylphosphate) at 0.16 ppm for the fifth dose, when the larval stages of the parasite revealed resistance to Unden.